Tourism competitiveness on the utilization zone of National Park in Indonesia - Fauziah Eddyono; Dudung Darusman; Ujang Sumarwan; Tutut Sunarminto (Jurnal Penelitian Kehutanan Wallacea, 2021)
Indonesia has various natural tourist attractions existed in the utilization zones of National Parks, scattered in regencies and cities within the archipelago. The utilization zone has a supportive environmental condition and very potential for the development of natural tourism, especially ecotourism. This utilization zone has endowment and added value in the form of attractions of Indonesia's unique ecosystem diversity. The utilization zone of Natural Park requires supporting elements in the form of tourism competitiveness in regencies and cities to make them more accessible to tourists, mostly foreign tourists, and also make it easier for tourists to meet their needs while traveling. This study aimed to analyze the effectiveness of tourism competitiveness factors in 54 areas of the utilization zone of National Park.This study design used 20 factors of tourism competitiveness.The data were analyzed using the cluster method and multidimensional scale, as well as the Importance Performance Analysis (IPA)approach. This study found three regional clusters based on the characteristics of the potential for tourism competitiveness, namely the outside regional cluster of Java and Bali Islands, cluster of Java Island, and cluster of Bali region. Based on the effectiveness of potential for competitiveness, each cluster can be classified as a priority scale for building and developing of tourism competitiveness. Therefore, it is necessary to propose to the central government, local governments, National Park management, and other related parties to innovate policies innovations through the Destination Management Organization(DMO)governance mechanism in an effort to optimize tourism competitiveness factors in their regions, so that ecotourism in their regions is competitive and sustainable